Nutritional Value of the Duckweed Species of the Genus Wolffia (Lemnaceae) as Human Food - Appenroth, Klaus-J.; Sree, K. Sowjanya; Bog, Manuela; Ecker, Josef; Seeliger, Claudine; Böhm, Volker; Lorkowski, Stefan; Sommer, Katrin; Vetter, Walter; Tolzin-Banasch, Karla; Kirmse, Rita; Leiterer, Matthias; et al. (Frontiers in Chemistry, 2018)
Species of the genus Wolffia are traditionally used as human food in some of the Asian countries. All eleven species of this genus, identified by molecular barcoding, were investigated for ingredients relevant to human nutrition. The total protein content varied between 20 and 30% of the freeze-dry weight, the starch content between 10 and 20%, the fat content between 1 and 5%, and the fiber content was approximately 25%. The essential amino acid content was higher or close to the requirements of preschool-aged children according to standards of the World Health Organization. The fat content was low, but the fraction of polyunsaturated fatty acids was above 60% of total fat and the content of n-3 polyunsaturated fatty acids was higher than that of n-6 polyunsaturated fatty acids in most species. The content of macro- and microelements (minerals) not only depended on the cultivation conditions but also on the genetic background of the species. This holds true also for the content of tocopherols, several carotenoids and phytosterols in different species and even intraspecific, clonal differences were detected in W. globosa and W. arrhiza. Thus, the selection of suitable clones for further applications is important. Due to the very fast growth and the highest yield in most of the nutrients, W. microscopica has a high potential for practical applications in human nutrition.